2016
DOI: 10.1371/journal.pntd.0005113
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Diagnostic Assays for Monitoring Single Nucleotide Polymorphisms in Necator americanus Associated with Benzimidazole Drug Resistance

Abstract: BackgroundSoil-transmitted helminths (STHs) are the most prevalent intestinal helminths of humans, and a major cause of morbidity in tropical and subtropical countries. The benzimidazole (BZ) drugs albendazole (ABZ) and mebendazole (MBZ) are used for treatment of human STH infections and this use is increasing dramatically with massive drug donations. Frequent and prolonged use of these drugs could lead to the emergence of anthelmintic resistance as has occurred in nematodes of livestock. Previous molecular as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 42 publications
0
48
0
Order By: Relevance
“…Anthelmintic resistance, including multidrug resistance [85], is a well documented issue in animal populations [86] and some mutations associated with benzimidazole resistance have been identified in eggs from human stool [87]. Although any largescale MDA with benzimidazoles may risk producing resistance [54], in animal husbandry, strategies to combat resistance include the exclusion of a subset of the population from deworming to maintain refugia [88,89].…”
Section: Theoretical Possibilities: What Do the Models Tell Us?mentioning
confidence: 99%
“…Anthelmintic resistance, including multidrug resistance [85], is a well documented issue in animal populations [86] and some mutations associated with benzimidazole resistance have been identified in eggs from human stool [87]. Although any largescale MDA with benzimidazoles may risk producing resistance [54], in animal husbandry, strategies to combat resistance include the exclusion of a subset of the population from deworming to maintain refugia [88,89].…”
Section: Theoretical Possibilities: What Do the Models Tell Us?mentioning
confidence: 99%
“…As shown in Figure 3, 2-(methoxycarbonylamino)-3H-benzimidazole-5-carboxylic acid (Hapten) not only has the general chemical structures of carbamate BZs, but it also has a carboxyl, which can conjugate with carrier protein directly. Compared with other haptens used in previous research, 1H-benzo[d] [1,2,3]triazol-1-yl6-((tert-butoxycarbonyl) amino) hexanoate [12a] and ABZNH 2 SO 2 [12c] had relatively large structure difference with BZs. Thus, it is more likely to get one antibody that can recognize different kinds of BZs simultaneously by using this hapten.…”
Section: Characterization Of Antigenmentioning
confidence: 99%
“…BZs have advantages of being broad spectrum and have high effectiveness and low toxicity. However, the abusing the use of BZs can lead to the emergence of drugresistant anthelmintics, [3] and can generate residues in foods of animal origin, such as milk and pork. [4] In addition, animal experiments showed that BZs had a certain embryo toxicity, polyploidy, and teratogenicity.…”
mentioning
confidence: 99%
“…This technique has been previously used to develop assays for the hookworm, N . americanus [30]. The SmartAmp2 is a DNA amplification method for detection of DNA mutations, deletions or SNPs under isothermal conditions and in a single step.…”
Section: Introductionmentioning
confidence: 99%